its answare is m=0,1,3

**m**

^{2}-4m+3 = 0**First Factor the Trinomial:**

**m**

^{2}-4m+3Trinomials have 3 terms. The 3 terms of this trinomial are: m

^{2}, -4m, and +3.Trinomials are formed by multiplying 2 binomials together. Binomials have 2 terms.

1. ( )( )

2. Factor the first term m

^{2}= m x m (m )(m )

3. The coefficient of the second term -4m, is

**-4** formed by adding the factors of the third term.

4. The third term +3 has the factors

**1, 3**or**-1, -3**. The pair of factors which add to give -4, is

**-1,-3**5. This gives the factors:

(m - 1 )(m - 3)

**Solve the Trinomial**

To solve this trinomial we must let it be = 0

m

^{2}-4m+3 = 0 (m - 1 )(m - 3)= 0

If (m - 1 )(m - 3)= 0 then at least 1 factor must be 0

Taking the first factor (m - 1):

if m-1 = 0

m-1 = 0

+1 =+1

**m = 1**

**if m-3 = 0**

m-3 = 0

+3 =+3

m = 3

m = 3

**The solution to the problem: m = 1, 3 NOT m = 0**